Linguocultural And Discursive Characteristics of Precedent Units in Sacred Texts - Zebokhon Mallayeva (American Journal Of Social Sciences And Humanity Research, 2026)
This study explores the linguocultural and discursive characteristics of precedent units in sacred texts, emphasizing their role in shaping collective cultural memory and interpretative frameworks. Precedent units, understood as culturally significant linguistic elements derived from canonical sources, function as key semiotic markers within religious discourse. The research aims to identify the structural, semantic, and pragmatic features of such units and to analyze their contribution to meaning construction in sacred texts. Methodologically, the study is based on a qualitative analysis of selected excerpts from major sacred texts, including the Bible and the Qur’an, employing linguocultural, discourse-analytic, and hermeneutic approaches. Particular attention is paid to intertextuality, symbolic representation, and the transmission of cultural values embedded in precedent phenomena. The findings reveal that precedent units operate as condensed carriers of cultural knowledge, enabling the reproduction of shared meanings across different historical and sociocultural contexts. They demonstrate a high degree of semantic density, symbolic complexity, and pragmatic flexibility. Discursively, these units function as cohesive devices that structure religious narratives, reinforce ideological positions, and facilitate interpretative engagement. The study concludes that precedent units in sacred texts serve not only as linguistic elements but also as powerful tools of cultural continuity and cognitive orientation. Their analysis contributes to a deeper understanding of the interaction between language, culture, and discourse, particularly in the context of religious communication. The results have significant implications for linguistics, cultural studies, and language pedagogy, especially in developing interpretative competence in literary and religious texts.